TECHNOLOGICAL ADVANCEMENTS AND COST CONTROL: INSIGHTS FROM CAS IMPLEMENTATION IN NIGERIA’S OIL INDUSTRY - Evelyn , Ifunanya Eze; Nwankwo, Michael Chinedu (Research Journal of Economics and Sustainable Development, 2024)
This study investigated the impact of computerized accounting systems (CAS) on the performance of Nigerian oil and gas firms in Port Harcourt with a capital base of over 500 million. A survey research design was adopted using questionnaires to collect primary data from 100 personnel in the accounting/finance and IT/ICT departments of five randomly selected firms. The study found a positive and significant effect of accounting software usage on accountability, productivity, and cost control in the oil and gas firms. The study recommends the use of electronic mediums and other alternative channels, such as cloud computing frameworks, for storing financial information to ensure the safeguarding of such information and prevent data loss, as well as the deployment of CAS in functional departments to boost efficiency and speed up the generation of internal and external financial reports. This study contributes to the existing literature, particularly as it focuses on the oil and gas sector in Nigeria, an area previously unexplored.